Efektifitas Penerapan Metode Cross-line Terhadap Hasil Belajar Siswa Kelas VI SDN 2 Sukosono - Nailufar, Daniela Arnesti; Sutriyani, Wulan (Universitas Negeri Makassar, 2024)
This research aims to obtain accurate information, description and knowledge about the effectiveness of applying the Cross-line method to the learning outcomes of material on the properties of multiplication of integers for class VI students at SD N 2 Sukosono. The Cross-line method is a method for calculating multiplication easily using intersecting lines. This type of research is quantitative research with the pre-experimental method. The type of design used is one group pretest-posttest. The research sample was all 22 class VI students at SD N 2 Sukosono, consisting of 12 girls and 10 boys. The data obtained was processed using the t test and showed a significance value (Sig.) of 0.002, which is smaller than the general significance level (0.05), indicating the effectiveness of applying the Cross-line method and influencing the learning outcomes of class VI students at SDN 2 Sukosono Especially in the material on the properties of multiplication of integers after being given an action or intervention using the Cross-line method.